Correlation of HbA1c levels in late pregnancy with maternal and perinatal outcome in patients with gestational diabetes mellitus - Kaur, Navjot; Goel, Poonam; Mehra, Reeti; Kaur, Jasbinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Estimation of HbA1c in gestational diabetes mellitus patients is not being recommended by any societies/guidelines as studies regarding the role of HbA1c for monitoring of euglycemic control and predicting the maternal and perinatal outcomes in GDM patients (unlike overt diabetes) are conflicting and sparse. Methods: This was a prospective study with an aim to evaluate the role of HbA1c estimation in late pregnancy (early and late third trimester) for prediction of pregnancy outcomes in GDM patients. 53 patients with GDM (diagnosed before third trimester) were recruited for the study. HbA1c levels were estimated in late pregnancy (at 28-32 weeks and again repeated at 37 - 39 weeks or at the time of delivery). Correlation of HbA1c levels in third trimester with maternal and perinatal outcome was studied in patients with gestational diabetes mellitus and cut off taken was 5.8%. Results: Of the total 53 patients 54.7% had HbA1c levels <5.8% and 45.3% had HbA1c ≥5.8% done at 28-32 weeks. Also when HbA1c levels done at 37-39 weeks POG/ at the time of delivery, 52.8% patients had <5.8% and 47.2% had HbA1c ≥5.8%. Approximately one-fourth of the patients had HbA1c ≥ 5.8% even with normal blood sugar levels (euglycemic) control. There was statistically significant increased incidence of polyhydramnios, LGA (large for gestational age babies) and increased mean birth weight in patients with HbA1c ≥ 5.8%, done in late pregnancy. However there was no statistically significant difference in the incidence of preterm labour, gestational hypertension or preeclampsia, urinary tract infections, vulvovaginal infections, caesarean deliveries and postpartum haemorrhage in patients with HbA1c ≥5.8% compared to patients with HbA1c <5.8%. Conclusions: The study revealed that in patients of GDM with HbA1c levels ≥5.8% done in third trimester was statistically significantly associated with increased incidence of polyhydramnios, large for gestational age babies and increased mean birth weight when compared to patients with HbA1c <5.8%.